2018
DOI: 10.1002/bjs5.67
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of aggregated length of stay after open and laparoscopic surgery for cancers of the digestive system

Abstract: BackgroundLength of hospital stay (LOS) may serve as a surrogate measure of healthcare quality and resource use, particularly when transfers of care and readmissions are accounted for. This study aimed to benchmark true hospital stay by measuring index, transfer and readmission stays across the range of digestive cancer surgery.MethodsA cohort study of all patients undergoing resection for cancer of the oesophagus, stomach, liver, pancreas, colon or rectum in 2012–2016 was undertaken. Index LOS, transfer and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Although it could be useful for risk adjustment, this study did not measure the severity of illness or the complexity and duration of the surgery. A recent Norwegian study of gastrointestinal cancer surgery concluded that an appropriate measure of LOS should include not only transfers, but also readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it could be useful for risk adjustment, this study did not measure the severity of illness or the complexity and duration of the surgery. A recent Norwegian study of gastrointestinal cancer surgery concluded that an appropriate measure of LOS should include not only transfers, but also readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…This was a longitudinal, observational national 5-year cohort study covering the universal health care system in Norway (from 1.1.2012 to 31.12.2016), as described in detail previously for nationwide data and time-trends [7,8,10] and consulting the guidelines for Strengthening the Reporting of Observational Studies in Epidemiology in Epidemiology (STROBE) [11].…”
Section: Methodsmentioning
confidence: 99%
“…The details of the inclusion and exclusion criteria have been presented previously [7,10]. Briefly, all Norwegian hospitals must submit data to the Norwegian Patient Registry (NPR) for registry and reimbursement purposes.…”
Section: Data From the Norwegian Patient Registry (Npr)mentioning
confidence: 99%
See 2 more Smart Citations